E-leadership: Concept and challenges - Farheen, Shabana (South Asian Journal of Socio-Political Studies)
Leadership is a social influence process which always involved a complex set of phenomena that require an interdisciplinary research. It is a classical topic for the scholars of management and administration. Leadership and management studies are coping with change and complexities simultaneously in the subject. Leadership is the ability to direct and guide a group of people in order to achieve a common goal along with management skills. Some people have the capacity to become good managers but not strong leaders, likewise others have great leadership but have difficulty in becoming strong managers. In this condition effective leaders are those who are able to inspire and motivate others to work together towards a shared vision. They possess a range of skills and qualities such as communication, decision-making and solving. Leadership can be exercised in a wide variety of settings, from business and government to sports and the arts. Ultimately, the most effective leaders are those who can able to foster a sense of teamwork and collaboration in the changing and complex situations.- Reproduced